2020
DOI: 10.5606/ehc.2020.70955
|View full text |Cite
|
Sign up to set email alerts
|

Sesamoid bones of the hand: A multicenter study

Abstract: This study aims to document a detailed investigation on the sesamoid bones (SBs) of Turkish subjects from different parts of Turkey in a multi-center study, in both hands, according to gender, frequency and divisions of the bones' coexistence and bilaterality by radiography. Patients and methods: This retrospective and three-centered study was performed between June 2010 and April 2012. Sesamoid bones were examined by anteroposterior and oblique X-rays of 1,444 hands of 772 subjects (367 males, 405 females; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 17 publications
2
18
2
Order By: Relevance
“…[3][4][5] In two studies from Turkey, both reported a prevalence of sesamoid at MCP II as 36.6%. [6,7] In the current study, we detected similar results as 37.61%.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…[3][4][5] In two studies from Turkey, both reported a prevalence of sesamoid at MCP II as 36.6%. [6,7] In the current study, we detected similar results as 37.61%.…”
Section: Discussionsupporting
confidence: 83%
“…[1,[3][4][5] Two previous studies from Turkey reported a similar MCP V sesamoid prevalence of the hand as 53.2% and 62.5%, respectively. [6,7] The prevalence of MCP V sesamoid (80%) in our study was significantly higher than previous two studies. This difference can be attributed to the accuracy of CT to determine the bony structures better.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations